Language Shift by the Javanese in Balee Village - Musliadi Musliadi; Rahmad Husein (LINGUISTIK TERAPAN, 2016)
This study deals with Javanese language shift in Balee Village, North Aceh. It aims to find out the factors of Javanese language shift into Acehnese language in Balee Village, North Aceh, the pattern of Javanese language shift and the reasons of Javanese language shift in Balee Village, North Aceh. The data were obtained from the family of Javanese living in Balee Village, North Aceh. The study employs qualitative research design with a single case study to get the understanding on this study. The subjects of this study were 10 families. The subjects were divided into two groups, namely parents and children. The findings showed that the shift of Javanese into Acehnese Language in Balee village, North Aceh was influenced by bilingualism, migration, economy, society, demography, institution, and attitudes. The Javanese language shift to Acehnese language occurred in the pattern of relationship between parents and children and among children. The shifts of Javanese to the Acehnese are mostly caused by social conflict. Keywords: language shift, Javanese, social conflict